Chaya: Mayan vegetable enriching diets year round in Mesoamerica - Bioversity International; Universidad del Valle (2017)
Chaya (Cnidoscolus acontifolius) was domesticated by Mayan peoples in pre-Columbian times. Due to its high nutritive value, tolerance to heat and drought, and minimal care requirements, this native vegetable has potential to support more nutrition-sensitive food systems in Mesoamerica. This fact sheet summarizes key features of this underutilized species.